A closer look into metastable effects of Cu(In, Ga)Se2 solar cells. Issue 6 (23rd February 2017) - Lavrenko, Tetiana; Walter, Thomas; Plesz, Balázs
Abstract : In this contribution, metastabilities of Cu(In, Ga)Se2 (CIGS)/CdS thin films are discussed based on photoluminescence (PL) imaging and complementary vibrating Kelvin probe (VKP) measurements. It has been shown that thermal treatment of CIGS/CdS thin films leads to the PL intensity quenching and a change in a surface band‐bending as deduced from VKP measurements under illumination. The impact of white light soaking has the opposite effect as compared to heat treatment: elevated temperatures enhance surface band‐bending whereas illumination leads to at least a partial band‐flattening. Furthermore, it has been found that etching away the CdS buffer layer reduces the previously measured band‐bending significantly pointing out the importance of the buffer layer deposition process. Moreover, the investigation of P1 scribes revealed that surface potentials in the vicinity of the patterning lines differ from the surface potentials measured on cells what is also reflected in the PL images as differences in the intensity between the bulk of the cells and P1 scribes. This observation suggests that the influence of P1 scribing parameters on electrical characteristics of CIGS solar cells has to be studied additionally as they can significantly affect the overall efficiency of the cell.